Taboo Words Used in the Hollywood Movie Walk of Shame - Sintha Handayani, Putu; Krisnawati, Ni Luh Putu (Humanis; Vol 22 No 3 (2018), 2018)
Another way to express feeling, relief from burden or show how intimate someone with another is by using taboo words; even though, it is a forbidden language. However, the using of taboo words can induce misunderstanding if it is used in inappropriate situation. Moreover, there are many taboo words used by characters in the Hollywood movies which can be imitated by people from other countries without knowing the proper meaning and situation to use them because in some context, some of taboo words can have another meaning and what is not taboo for someone may be taboo for others. Seeing this phenomenon, the aims of this study are to classify types and find the functions of taboo words. The data source is one of the Hollywood movies entitled Walk of Shame . Therefore, people can be more aware to use taboo words. Some methods and techniques were applied for this research. In collecting data, content-analysis method and observation and note taking techniques were used. The following step was analysing the collected data. Qualitative method was used and the analysis techniques were collecting, reducing and classifying. The method in presenting the result is descriptive method; the result of the analysis is presented and explained in details by using words and sentences. The Theory proposed by Jay (1992) is combined with the theory proposed by Halliday and Hasan (1985); those are used to classify types of taboo words. Moreover, the theory proposed by Liedlich (1975) is used to find the function of using it. Six of ten types of taboo words were found; they are cursing, profanity, slang, ephitets, vulgarity, as well as insult and slur. Moreover, there were six functions of using taboo words found, they are creating attention, discredit, endearment, creation of strong interpersonal identification, provoking violent confrontation, and providing catharsis.